Peran Lembaga Pengembangan Tilawati Qur’an (LPTQ) dalam Meningkatkan Kemampuan Literasi Al-Qur’an Masyarakat di Kecamatan Tanjung Morawa - Fahrozy Pradana Putra; Mohammad Al Farabi (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2023)
This research aims to describe and analyze the role of LPTQ in increasing people's interest in reading the Al-Qur'an and identify factors that support and hinder the role of increasing people's Al-Qur'an literacy skills. To achieve this goal, researchers used qualitative methods in the form of field research. Data collection techniques were carried out using observation, interviews and document study. In analyzing the data using the Miles and Huberman pattern which consists of data reduction, data presentation and drawing conclusions. The research results show that there is a role for LPTQ in improving the community's Al-Qur'an literacy skills which is carried out through several roles or activities such as (1) Al-Qur'an reading and writing training, (2) recitation training activities and recitation knowledge, (3) Religious studies that examine the contents of the Al-Qur'an as an effort to prevent teenagers from delinquency, promiscuity, drugs and criminal acts.